2018
DOI: 10.5530/jyp.2018.10.42
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal Plants Used for the Treatment of Malaria in Malaka, West Timor

Abstract: Objective: This study aims to document ethnomedicinal plants used in the traditional treatment of malaria in some areas of Malaka District in West Timor, Indonesia. Methods: Semi-structured questionnaire interviews and focused group discussion were used to gather ethnomedicine data from traditional healers and people who know about traditional medicines. The study involved 38 informants, 30 women and 8 men, aged between 32-90 years, from 10 villages in 4 sub-districts. Results: A total of 44 plants species bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…For example, Keo et al (2018) documented 50 species of medicinal plants in Cambodia that have been customarily used to treat common ailments while the survey of Sharmila et al (2018) on some plant species in Nainamalai Foothill in the Eastern Ghats recorded a total of 124 plants used in a variety of medicinal applications. Meanwhile, the study of Taek et al (2018) reported several ethnomedicinal plants as treatment for malaria in Malaka, West Timor. On the other hand, the findings of Zain-ul-Abidin et al (2018) revealed that 40 highly anti-diabetic plant species used in South Pakistan for the treatment and control of diabetes mellitus type II are reported for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Keo et al (2018) documented 50 species of medicinal plants in Cambodia that have been customarily used to treat common ailments while the survey of Sharmila et al (2018) on some plant species in Nainamalai Foothill in the Eastern Ghats recorded a total of 124 plants used in a variety of medicinal applications. Meanwhile, the study of Taek et al (2018) reported several ethnomedicinal plants as treatment for malaria in Malaka, West Timor. On the other hand, the findings of Zain-ul-Abidin et al (2018) revealed that 40 highly anti-diabetic plant species used in South Pakistan for the treatment and control of diabetes mellitus type II are reported for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…Many Tetun people do not consider mosquito as carrier of malaria, causing them to have low awareness of the threat of mosquitoes. This may be one of the causes of the still high endemic of malaria in Belu and Malaka until this time 21 …”
Section: Discussionmentioning
confidence: 99%
“…The leaves are pounded well to get juicy extract, mix it with little kerosene and applied externally on the skin to treat diseases like allergies, acne, and ringworm by the Subanen communities in Gala and Guimad villages in Ozamis City, Mindanao, the Philippines (Alduhisa and Demayo 2019). Indonesia: Stem barks are used as drug for the treatment of Malaria by native people in Malaka, West Timor (Taek et al 2018).…”
Section: Local Medicinal Usesmentioning
confidence: 99%